A mixed methods evaluation of a World Health Organization competency-based training package for foundational helping skills among pre-service and in-service health workers in Nepal, Peru and Uganda - Gloria A. Pedersen; Pragya Shrestha; Josephine Akellot; Alejandra Sepulveda; Nagendra P. Luitel; Rosco Kasujja; Carmen Contreras; Jerome T. Galea; Leydi Moran; Vibha Neupane; Damodar Rimal; Alison Schafer; et al. (Cambridge Prisms: Global Mental Health, 2023)
Health systems globally demand more competent workers but lack competency-based training programs to reach their goals. This study evaluates the effectiveness of a competency-based curriculum (EQUIP-FHS) for trainers and supervisors to teach foundational helping knowledge, attitudes and skills, guided by the WHO/UNICEF EQUIP platform, to improve the competency of in-service and pre-service workers from various health and other service sectors. A mixed-methods, uncontrolled before-and-after trial was conducted in Nepal, Peru, and Uganda from 2020 to 2021. Trainees’ (N = 150) competency data were collected during 13 FHS trainings. Paired t-tests assessed pre- to post-change in ENACT competency measures (e.g., harmful, helpful). Qualitative data was analyzed using thematic analysis. EQUIP-FHS trainings, on average, were 20 h in duration. Harmful behaviors significantly decreased, and helpful behaviors significantly increased, across and within sites from pre-to post-training. Qualitatively, trainees and trainers promoted the training and highlighted difficult competencies and areas for scaling the training. A brief competency-based curriculum on foundational helping delivered through pre-service or in-service training can reduce the risk that healthcare workers and other service providers display harmful behaviors. We recommend governmental and nongovernmental organizations implement competency-based approaches to enhance the quality of their existing workforce programming and be one step closer to achieving the goal of quality healthcare around the globe.